THE EFFECT OF PHYSICAL ACTIVITY ON BLOOD SUGAR AND CHOLESTEROL LEVELS AMONG PEOPLE WITH DIABETES MELLITUS - Suprayitna, Marthilda; Fatmawati, Baiq Ruli; Prihatin, Kurniati (Nurse and Holistic Care, 2022)
Background: Diabetes mellitus is a chronic metabolic disorder characterized by hyperglycemia which can cause acute and chronic complications. Uncontrolled hyperglycemia could lead to high cholesterol that forms in fat metabolism to accumulate and threaten blood vessels. Physical activity is one of the pillars of diabetes mellitus management to reduce blood sugar and cholesterol. Objective: This research aimed to determine the effect of physical activity on blood sugar and cholesterol levels in diabetes mellitus patients in the working area of Cakranegara Public Health Center. Methods: This research is Quasi-experimental with one group pretest-posttest design without a control approach. The numbers of samples used in this research were 17 people, selected by purposive sampling technique. Data analysis used in this research were univariate and bivariate using Paired T-Test. Result: Based on the Paired T-test analysis, it shows that physical activity was proven to have an effect in reducing blood sugar levels with a ρ-value of 0.000 (<0.05) and cholesterol with a ρ value of 0.000 (<0.05). Conclusion: Based on the results, physical activity reduced blood sugar and cholesterol levels in patients with diabetes mellitus.